2020
DOI: 10.1159/000510038
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Motivation: Exploring the Roles of Prolactin and Pup Stimuli

Abstract: All rights reserved. No part of this publication may be translated into other languages, reproduced or utilized in any form or by any means, electronic or mechanical, including photocopying, recording, microcopying, or by any information storage and retrieval system, without permission in writing from the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…The enormous investment of time and energy that these behaviors require may explain why females only exhibit fully motivated maternal behavior during peripartum (for a review see Kohl et al, 2017;Salais-López et al, 2020). Although maternal behaviors are normally expressed after delivery, when pups are present, they are already facilitated during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The enormous investment of time and energy that these behaviors require may explain why females only exhibit fully motivated maternal behavior during peripartum (for a review see Kohl et al, 2017;Salais-López et al, 2020). Although maternal behaviors are normally expressed after delivery, when pups are present, they are already facilitated during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, maternal aggression might require a certain degree of motivation to attack as well as a learning process, e.g., the first encounter with an intruder approaching the nest would not result in immediate, effective attacks. In fact, recent results from our lab show that, whereas virgin females co-housed with dams are as quick as dams in classic pup retrieval tests 9 , they are significantly slower in learning to retrieve pups in a "motivated pup retrieval test" in which they need to climb a barrier to access pups 16 . Thus, one could hypothesise a similar situation for maternal aggression, i.e., pup-sensitized virgins co-housed with dams could develop aggressive responses after repeated confrontations with intruders.…”
Section: Introductionmentioning
confidence: 87%
“…Thus, one could hypothesise a similar situation for maternal aggression, i.e., pup-sensitized virgins co-housed with dams could develop aggressive responses after repeated confrontations with intruders. By contrast, CD1 virgin females that are not co-housed with dams, but only to pups for two hours per day, needed three days to achieve a performance comparable to that of dams in a classical pup-retrieval test 9 and did not perform any retrieval in the "motivated pup retrieval test" 16 . Thus, in the present study we first characterized how repeated exposure towards an intruder male could affect the onset and features of social and aggressive behaviours of dams and their pair-housed pup-sensitized virgins.…”
Section: Introductionmentioning
confidence: 91%
“…Studies that specifically focus on the role of lactogenic hormones in maternal motivation have recently started to emerge. A first study reported correlational findings of a link between high maternal motivation in a barrier climbing test and increased Prlr signaling (as measured by pSTAT5 immunoreactivity) in several brain regions, including the MPOA, MeA, PVN, and posterior intralaminar thalamic nucleus (PIL) ( 47 ). Increased pSTAT5 immunoreactivity was also found in the MPOA and PIL of pup-experienced virgins that showed increased maternal motivation in this test ( 47 ).…”
Section: Offspring-directed Behaviors (Retrieval Licking Nursing and Grooming)mentioning
confidence: 99%
“…A first study reported correlational findings of a link between high maternal motivation in a barrier climbing test and increased Prlr signaling (as measured by pSTAT5 immunoreactivity) in several brain regions, including the MPOA, MeA, PVN, and posterior intralaminar thalamic nucleus (PIL) ( 47 ). Increased pSTAT5 immunoreactivity was also found in the MPOA and PIL of pup-experienced virgins that showed increased maternal motivation in this test ( 47 ). Recently we have shown a causal relationship between lactogenic action in the brain and maternal motivation.…”
Section: Offspring-directed Behaviors (Retrieval Licking Nursing and Grooming)mentioning
confidence: 99%